Reação de genótipos de algodoeiro à Sclerotinia sclerotiorum. - Pestana, Jeferson Rodrigo (2017)
The upland cotton is one of the main species domesticated by man, being the only one with the economic purpose of producing fiber. Brazil is the fifth largest cotton producer in the world. The expansion into irrigated and elevated areas also brought problems, such as an increase in the incidence of diseases previously classified as secondary like the white mold of cotton, a fungal disease caused by Sclerotinia sclerotiorum Lib. De Bary. Although genetic resistance is of extreme importance for the integrated management of the disease, there are few studies related to the topic. The objectives of this work were to evaluate the resistance of cotton genotypes to S. sclerotiorum, determine the best environment for the evaluation of resistance to disease, the aggressiveness of isolates from soybean and cotton, and the correlation between oxalic acid method and method straw test for cotton. Three experiments were carried out at the Laboratory of Mycology and Plant Protection of the Universidade Federal de Uberlândia between September and December 2016, two using the straw test method, one in greenhouse and the other in a growth chamber with a temperature of 22 ± 3ºC, and an experiment by the indirect method of oxalic acid. The inoculation of the 33 genotypes of cotton with two isolates of the fungus occurred when the plants reached phenological stage V2 with fungal mycelium, inserted in Eppendorf type tip and fixed on the apex of the plant after the removal of the apical meristem through cutting off. The length (cm) and severity (%) of the lesion in the stem of the plant were evaluated 7 days after inoculation, and wilt note (1-5) by the oxalic acid method. For the straw test, the experimental design was a randomized block design, in a factorial scheme with one inoculum from soybean, one from cotton and one control without inoculum and 33 genotypes, with three replicates and the experiment by oxalic acid method was block factorial with four conditions and three replicates. The data were submitted to analysis of variance, joint variance, Scott Knott's means separation test (p <0.05) and Genetic divergence was estimated from the Euclidian distance and the genotypes grouped by the hierarchical method UPGMA (Unweighted Pair Group Method with Arithmetic Mean) and non-hierarchical Tocher optimization. Through the analysis of the data, it was verified that the growth chamber environment provided more adequate conditions for S. sclerotiorum infection. The difference in aggressiveness between soybean and cotton isolates was observed, which cotton isolate reflected higher lesions in cotton plants. The most susceptible genotype, both by lesion size and severity, were the cultivars FM975 WS, TMG44 B2RF e BRS293, while the most resistant were FM944 GL, MAC-2 and IMA2106 GL. Based on the UPGMA and Tocher grouping methods, it was verified that the evaluated genotypes differ from each other. No correlation was verified between oxalic acid and straw test methods.